Neorickettsia sp. in coatis (Nasua nasua) in Brazil - Perles, Lívia [UNESP]; Barreto, Wanessa Teixeira Gomes; de Macedo, Gabriel Carvalho; Herrera, Heitor Miraglia; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (My University, 2023)
The genus Neorickettsia comprises trematode-associated bacteria that can cause diseases in animals and humans. Despite detection of Neorickettsia antigens in the intestine of coatis kept in captivity in southern Brazil through immunohistochemistry, the molecular identity of the bacteria in South American procyonids remains elusive. The aim of the present study was to investigate the occurrence of Neorickettsia sp. in blood samples from coatis in central-western Brazil. Between March 2018 and January 2019, animals were captured and recaptured in two areas of the Cerrado (Parque Estadual do Prosa, PEP; and Vila da Base Aérea, VBA) located in the city of Campo Grande, state of Mato Grosso do Sul, central-western Brazil. All captures were performed according to convenience. DNA from 97 blood samples was subjected to nested PCR (nPCR) targeting a fragment of the 16S rRNA gene of Neorickettsia sp. Six samples (3.6%; five from VBA and one from PEP) from different coatis were positive in nPCR based on the 16S rRNA. The sequences obtained (~500 bp) showed ˃ 99% similarity to N. risticii. Phylogenetic analysis clustered the sequences detected in the present study in a clade with N. risticii. This is the first molecular detection of Neorickettsia sp. in coatis in Brazil.
Neorickettsia sp. em quatis (Nasua nasua) no Brasil
Keywords: Anaplasmataceae; Central-Western Brazil; procyonidae